2007
DOI: 10.1016/j.foodchem.2006.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and preparation of bovine lactoperoxidase and characterization of kinetic properties of its immobilized form incorporated into cross-linked alginate films

Abstract: Lactoperoxidase (LPS), purified directly from bovine rennet whey by Toyopearl-SP cation-exchange chromatography and lyophilized by using dextran as supporting material, maintained almost 70 and 60% of its activity after almost 2 and 5 months storage at À18°C, respectively. Incorporation of the prepared LPS into alginate films between 0.08 and 0.69 mg/cm 2 (516-4325 U/cm 2 ) caused the immobilization of most of the enzyme and gave films with LPS activity between 0.05 and 2.8 U/cm 2 , determined in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The enzyme was prepared according to the method of Mecitoğlu and Yemenicioğlu (2007). For this purpose, LPS active fractions were pooled and dialyzed (cut off: 12.000 MW) for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme was prepared according to the method of Mecitoğlu and Yemenicioğlu (2007). For this purpose, LPS active fractions were pooled and dialyzed (cut off: 12.000 MW) for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in our laboratories, the LPS has also been incorporated into alginate films. The enzyme incorporated into these edible films bound and immobilized effectively onto films following cross‐linking and it shows appropriate stability and activity at a broad temperature and pH range (Mecitoğlu and Yemenicioğlu 2007). In this study, the antimicrobial activity of LPS incorporated into alginate films and its components has been tested on different bacteria including E. coli , Listeria innocua , and Pseudomonas fluorescens.…”
Section: Introductionmentioning
confidence: 99%
“…Purification of LPO was the subject of study for many research groups using various purification techniques. Ammonium sulfate precipitation in combination with cation‐exchange chromatography14 and gel filtration chromatography11 resulted in 50–64% and 28% recovery of LPO, respectively. These conventional techniques involved multi‐step procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Ozdemir et al .,[8] Nandini and Rastogi[27] and Mecitoğlu and Yemenicioğlu[9] used different successive methodes for separation LPO from bovine milk. However, by simply removing step of globulins, we use only CM-cellulose ion-exchange chromatography which is cost effective and short time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Mecitoğlu and Yemenicioğlu using toyopearl-sp Cation-exchange chromatography purified the enzyme. [9] In addition, affinity chromatography was used for the purification of LPO. [10] All of the research on the LPO purification have indicated that purification of the LPO can be performed using very-time consuming and complicated methods.…”
Section: Introductionmentioning
confidence: 99%